Step 1:
The time period of a spring-mass system is given by the formula:
\[ T = 2\pi \sqrt{\frac{m}{k}} \]
where:
\begin{itemize}
\item $T$ is the time period
\item $m$ is the mass
\item $k$ is the spring constant
\end{itemize}
For the given systems:
\begin{enumerate}
\item System (a):
\[ T_a = 2\pi \sqrt{\frac{m}{k}} \]
\item System (b): The spring constant is halved, i.e., $k' = \frac{k}{2}$. Therefore,
\[ T_b = 2\pi \sqrt{\frac{m}{k/2}} = 2\pi \sqrt{\frac{2m}{k}} = \sqrt{2} \left( 2\pi \sqrt{\frac{m}{k}} \right) = \sqrt{2} T_a \]
\item System (c): The spring constant is doubled, i.e., $k'' = 2k$. Therefore,
\[ T_c = 2\pi \sqrt{\frac{m}{2k}} = \frac{1}{\sqrt{2}} \left( 2\pi \sqrt{\frac{m}{k}} \right) = \frac{1}{\sqrt{2}} T_a \]
\end{enumerate}
Thus, the ratio of the time periods is:
\[ T_a : T_b : T_c = 1 : \sqrt{2} : \frac{1}{\sqrt{2}} \]